PREDICTING CUSTOMER SATISFACTION AND INTENTION TO REVISIT AT LOCAL COFFEE SHOP WITH INDUSTRIAL CONCEPT IN JAKARTA - Bagas Mufhtie Haifa; Usep Suhud; Shandy Aditya (Universitas Terbuka, 2021)
This study examines the factors that influence customer satisfaction and visiting intentions at a local industrial coffee shop. This study uses six measured variables: service quality, food quality, variety of menu, café atmosphere, customer satisfaction and revisit intention. The data collection method used a survey with an instrument in the form of a online questionnaire. Respondents are those who live in DKI Jakarta and have made purchases and visits to local coffee shop with industrial concepts. A total of 246 respondents were involved, the data were analyzed using SPSS 26 and SEM from AMOS software version 26 to manage and analyze data. The results of this study based on the hypothesis indicate that the hypothesis of service quality on revisit intention is accepted and significant, service quality on customer satisfaction is accepted and significant, food quality on revisit intention is accepted and significant, food quality on customer satisfaction is accepted and significant, customer satisfaction on revisit intention is accepted. and significant, variety of menu on customer satisfaction is accepted and significant, variety of menu on revisit intention is accepted and significant, café atmosphere on customer satisfaction is accepted and significant, café atmosphere on revisit intention is accepted and significant.